5E- and 5Z-farnesylacetones from Sargassum siliquastrum as novel selective L-type calcium channel blockers - Shin, Woon-Seob; Oh, Sangtae; An, Sung-Wan; Park, Gab-Man; Kwon, Daeho; Ham, Jungyeob; Lee, Seokjoon; Park, Byong-Gon (ELSEVIER SCIENCE INC, 2013)
A specific blocker of L-type Ca2+ channels may be useful in decreasing arterial tone by reducing the open-state probability of L-type Ca2+ channels. The aim of the present study was to evaluate the farnesylacetones, which are major active constituents of Sargassum siliquastrum, regarding their vasodilatation efficacies, selectivities toward L-type Ca2+ channels, and in vivo antihypertensive activities. The application of 5E-(famesylacetone 311) or 5Z-farnesylacetone (farnesylacetone 312) induced concentration-dependent vasodilatation effects on the basilar artery that was pre-contracted with depolarization and showed an ignorable potential role of endothelial-derived nitric oxide. We also tested farnesylacetone 311 or 312 to determine their pharmacological profiles for the blockade of native L-type Ca2+ channels in basilar arterial smooth muscle cells (BASMCs) and ventricular myocytes (VMCs), cloned L-(alpha 1C/beta 2a/alpha 2 delta), N-(alpha 1B/beta 1b/alpha 2 delta), and T-type Ca2+ channels (alpha 1G, alpha 1H, and alpha 1I). Farnesylacetone 311 or 312 showed greater selectivity toward the L-type Ca2+ channels among the tested voltage-gated Ca2+ channels. The ranked order of the potency for farnesylacetone 311 was cloned alpha 1C L-type (BASMC) L-type (VMCs)>alpha 1B>alpha 1H>alpha 1I>alpha 1G and that for famesylacetone 312 was cloned alpha 1C L-type (BASMCs) L-type (VMCs)>alpha 1H>alpha 1G>alpha 1B>alpha 1I. The oral administration of the famesylacetone 311 (80 mg/kg) conferred potent, long-lasting antihypertensive activity in spontaneous hypertensive rats, but it did not alter the heart rate. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: SPONTANEOUSLY HYPERTENSIVE-RATS; HIGH BLOOD-PRESSURE; SMOOTH-MUSCLE-CELLS; GATED ION CHANNELS; RESISTANCE ARTERIES; SYMPATHETIC NEURONS; CA2+ CHANNELS; WISTAR-KYOTO; PHARMACOLOGY; DEPOLARIZATION